Vitamin D Status in Sample of Iraqi Women with Autoimmune Thyroiditis - Wasan R. J. Al-Jorany, Makarim Q. D. Al-Lami (Pakistan Journal of Medical & Health Sciences, 2023)
The most common cause of acquired thyroid dysfunction is autoimmune thyroid disease (AITD), which most commonly manifests as Hashimoto’s thyroiditis (HT) or Graves’ disease (GD). The importance of vitamin D (vit D) as an immune modulator has recently been emphasized in several types of disorders. However, its significance in thyroid illnesses is not fully understood. The purpose of this study is to investigate how vitamin D affects the pathophysiology of hyperthyroidism and hypothyroidism in Iraqi women. One hundred Iraqi women with age ranged from 18 to 60 years participate in this research, 50 of them were hypothyroidism patients, 30 were hyperthyroidism patients and the other 20 were euthyroidism served as controls. Blood samples were collected from the studied subjects to determine thyroid profile [free triiodothyronine (FT3), free tetraiodothyronine (FT4) and thyroid stimulating hormone (TSH)], thyroid antibodies [anti-thyroid peroxidase (anti-TPO), anti-thyroglobulin (anti-Tg), and anti-thyroid stimulating hormone receptor (anti-TSHR)], vit D, calcium (Ca), and phosphorus (P) using different analysis techniques. Levels of FT3 and FT4 revealed a significant (P<0.01) increase in hyperthyroidism patients and a significant (P<0.01) decrease in hypothyroidism patients compared with euthyroidism control. While level of TSH was significantly (P<0.01) decreased in hyperthyroidism patients and significantly (P<0.01) increased in hypothyroidism compared with euthyroidism control. When a comparison was made between hyperthyroidism group and hypothyroidism group, the results showed that levels of FT3 and FT4 were significantly (P<0.01) higher in hyerthyroidism than hyporthyroidism while level of TSH was significantly (P<0.01) lower in hyperthyroidism than hyporthyroidism. Levels of anti-TPO and anti-Tg significantly (P<0.01) increased in hyperthyroidism and hypothyroidism patients compared with euthyroidism individuals, while level of anti-TSHR was significantly (P<0.01) decreased in hyperthyroidism patients and significantly (P<0.01) increased in hypothyroidism patients compared with euthyroidism individuals. On the other hand, the findings revealed that level of anti-TPO was significantly (P<0.01) higher while levels of anti-Tg and anti-TSHR were significantly (P<0.01) higher in hypothyroidism than hyperthyroidism. The results revealed a significant (P<0.01) decrease in level of vit D in hyperthyroidism patients and hypothyroidism patients compared with euthyroidism control, a significant (P<0.01) increase in levels of Ca and P in hyperthyroidism patients compared with euthyroidism control, while non-significant (P>0.01) differences were found between hypothyroidism patients and euthyroidism control. Also, the findings revealed that levels of vit D, Ca, and P were significantly (P<0.01) higher in hyperthyroidism than hypothyroidism. Conclusion: It can be concluded that Vit D deficiency may be act as a factor in both hyperthyroidism and hypothyroidism, and the status of vit D impact on autoimmune thyroiditis. Keyword: Autoimmune thyroiditis, Vitamin D, Hyperthyroidism, Hypothyroidism, Euthyroidism